2019
DOI: 10.1186/s12974-019-1452-1
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 inhibits interleukin-1β production and inflammasome activation of microglia in epileptic seizures

Abstract: Background Microglia are important for secreting chemical mediators of inflammatory responses in the central nervous system. Interleukin (IL)-10 and IL-1β secreted by glial cells support neuronal functions, but the related mechanisms remain vague. Our goal was to demonstrate the efficacy of IL-10 in suppressing IL-1β and in inflammasome activation in mice with epileptic seizure based on an epileptic-seizure mouse model. Methods In this study, mice in which epileptic sei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 60 publications
5
62
0
3
Order By: Relevance
“…First, IL-10 overexpression results in a reduction in NLRP3 inflammasome activity, which suppresses caspase-1-dependent IL-1b maturation. Second, autocrine IL-10 promotes activation and transduction of transcription-3, reducing the abundance of pro-IL-1b (Sun et al, 2019). Our study showed that liraglutide reduced intimal hyperplasia via downregulation of the NLRP3 inflammasome and upregulation of IL-10.…”
Section: Discussionmentioning
confidence: 57%
“…First, IL-10 overexpression results in a reduction in NLRP3 inflammasome activity, which suppresses caspase-1-dependent IL-1b maturation. Second, autocrine IL-10 promotes activation and transduction of transcription-3, reducing the abundance of pro-IL-1b (Sun et al, 2019). Our study showed that liraglutide reduced intimal hyperplasia via downregulation of the NLRP3 inflammasome and upregulation of IL-10.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, it has been speculated that amentoflavone, a natural biflavone compound with anti-inflammatory and antioxidative properties, has the ability to affect epileptogenesis and exerts neuroprotective effects through the inhibition of the NLRP3 inflammasome [ 248 ]. Interestingly, IL-10 administration in the picrotoxin seizure model results in a decreased activation of the NLRP3 inflammasome, thus of IL-1β release, suggesting a protective role in status epilepticus (SE) [ 249 ]. The role of NLRP3 inflammasome in the development of epilepsy was confirmed by a recent study showing that children with febrile seizures have higher serum levels of IL-1β, correlated to NLRP3 upregulation in PBMCs, as compared to healthy controls [ 250 ].…”
Section: The Neuroinflammatory Process In Epilepsy: the Involvemenmentioning
confidence: 99%
“…IL‐10 possesses anti‐inflammatory properties through activation of JAK1/STAT3 signaling that inhibits NF‐kB to suppress proinflammatory cytokine expression . This pathway has been implicated in epilepsy; using hippocampal cultures from a picrotoxin‐mediated seizure model in mice, IL‐10 overexpression was able to suppress IL‐1β expression . Using the closed cortical impact model of TBI, M2 polarization was induced by IL‐10 secretion from transplanted, genetically modified MSCs .…”
Section: Approaches To Induce Microglia M2 Polarization: Potential Agmentioning
confidence: 99%
“…74 This pathway has been implicated in epilepsy; using hippocampal cultures from a picrotoxin-mediated seizure model in mice, IL-10 overexpression was able to suppress IL-1β expression. 75 Using the closed cortical impact model of TBI, M2 polarization was induced by IL-10 secretion from transplanted, genetically modified MSCs. 76 The M2 polarized microglia in the CA1 area of the hippocampus led to improvements in fine motor skills and prevented cell loss.…”
Section: Exposure To M2-promoting Cytokinesmentioning
confidence: 99%